Molecular Confirmation of the Presence of Coliforms in Drinking Water Using Polymerase Chain Reaction - Tharannum, Seema; Sunitha, Sarah; Nithya, J.; Chandini, M.; Manitha, J.; Manjula, T. S.; Shyam Sundar, C. (Kathmandu University Journal of Science, Engineering and Technology, 2009)
Coliform bacteria include organisms like Escherichia coli, Enterobacter, Klebsiella, and Citrobacter. They are gram-negative, facultative anaerobic, non-sporulating, and lactose-fermenting organisms. E. coli is used as the indicator organism for detection of fecal contamination of water. Conventional methods for the detection of these Coliforms in water include microbial culture assays in lactose-containing media and enzyme-based assays for the detection of β-galactosidase using chromogenic substrates like ortho-nitrophenyl-β-D-galactopyranoside. These methods are cumbersome with limited specificity. DNA-based molecular techniques like Polymerase Chain Reaction (PCR) are recommended since they are highly specific. In this paper, we report the use of PCR for the amplification of the Lac Z (β-galactosidase encoding) gene to confirm the isolation of Coliform bacteria from drinking water samples. The method could be an effective epidemiological tool to pinpoint the source and contain outbreaks of waterborne disease episodes.